Combining Visualization and Statistical Analysis to Improve Operator Confidence and Efficiency for Failure Detection and Localization - Bodík, Peter; Friedman, Greg; Biewald, Lukas; Levine, Helen; Candea, George; Patel, Kayur; Tolle, Gilman; Hui, Jon; Fox, Armando; Jordan, Michael I.; Patterson, David (ICAC '05: International Conference on Autonomic Computing, 2005)
Web applications suffer from software and configuration faults that lower their availability. Recovering from failure is dominated by the time interval between when these faults appear and when they are detected by site operators. We introduce a set of tools that augment the ability of operators to perceive the presence of failure: an automatic anomaly detector scours HTTP access logs to find changes in user behavior that are indicative of site failures, and a visualizer helps operators rapidly detect and diagnose problems. Visualization addresses a key question of autonomic computing of how to win operators’ confidence so that new tools will be embraced. Evaluation performed using HTTP logs from Ebates.com demonstrates that these tools can enhance the detection of failure as well as shorten detection time. Our approach is application-generic and can be applied to any Web application without the need for instrumentation.